The inflorescence ofCyperus giganteusVahl (Cyperaceae) - Perreta, Mariel Gladis (2002)
The inflorescence of Cyperus giganteus VAHL is characterized considering its typological features, and compared with the structural patterns described for other Cyperaceae inflorescences.Cyperus giganteus VAHL is characterized considering its typological features, and compared with the structural patterns described for other Cyperaceae inflorescences.